Pengaruh Penggunaan Sistem Pembayaran Digital terhadap Perilaku Beralih di Era Pandemi COVID-19 - Rasistia Wisandianing Primadineska (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study aims to examine the effect of changes in individual behavior in the use of electronic payment systems on switching intentions and switching behavior of individuals during the COVID-19 pandemic in Indonesia. Total of 100 respondents from various regions in Indonesia were tested in this study. Most of the respondents are generation Z and millennial. The data were processed using SEM PLS. The results show that during the pandemic, individuals who have already used digital payment systems have the intention of switching from conventional to digital payment systems. The intention to switch has also had a positive effect on the behavior of moving from conventional to digital payment systems. This research adds references to behavioral research related to the development of the payment system in Indonesia, especially during the pandemic.